Kemandirian Petani dalam Mengelola Usahatani Sayuran di Kota Denpasar - I WAYAN SUCITAYASA; DWI PUTRA DARMAWAN; I NYOMAN GEDE USTRIYANA (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2018)
Self-Reliance of Farmers in Managing Vegetable Farming in Denpasar City The development of urban agriculture has many challenges such as the difficulty ofobtaining production inputs, the difficulty of obtaining credit, the limited ofresources, the limited time, and the agricultural sector which is not a priority sector.Difficulties in farming in urban areas can be minimized with the self-sufficiency ofeach farmer. The purpose of the study was to investigate how the performance ofvegetable farming management and how the level of self-sufficiency of vegetablefarmers in Denpasar, as well as what factors influence the self-sufficiency ofvegetable farmers in the city of Denpasar in terms of capital, production andmarketing that are categorized in three classes of measurement i.e. less selfsufficiency,moderate self-sufficiency or full self-sufficiency analyzed by qualitativedescriptive method. The results showed that vegetables farming conducted byfarmers in the city of Denpasar was still classified as a traditional that rely on habits.The self-sufficiency seen from the aspects of capital, production and marketing canbe categorized as medium category. Factors that affect the self-sufficiency in thecapital aspect was age. The self-sufficiency in the aspects of production wasinfluenced by the source of information, and the self-sufficiency in the marketingaspect was influenced by the partnership relationship. Based on the results of theresearch, it is recommended to increase the extension to increase knowledge offarmers related to vegetable agribusiness.